Increasing identity and community awareness in Medan City about victim rights of sexual violence - Sirait, Ningrum Natasya; Rosmalinda; Ikhsan, Edy; Siregar, Mahmul; Agusmidah (Talenta Publisher, 2019)
Indonesia currently has Law Number 11 of 2012 concerning the Criminal Justice System for Children (UU-SPPA) to provide protection for children who need special protection such as child offenders, victims and witnesses. In fact, the implementation of the UU-SPPA actually only focuses on children as perpetrators. This not only shows that justice for children is still not upright especially for children who are victims of sexual violence. This is evident from the findings of a study conducted in 2019 entitled